2020
DOI: 10.21203/rs.2.18737/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vitamin D status among postmenopausal osteoporotic women: a hospital based cross-sectional study from Northern Sri Lanka.

Abstract: Background Vitamin D deficiency is common among post-menopausal women and it is important to treat vitamin D deficiency to prevent falls and fractures in patients with osteoporosis. Few studies examined the prevalence of vitamin D deficiency in general population of Sri Lanka but no studies to date done among post-menopausal women with osteoporosis. This is the first study of such kind conducted to evaluate the serum vitamin D levels and factors related to Vitamin D deficiency among postmenopausal women.Method… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Some research has suggested that vitamin D may have a direct (through its function in pancreatic beta-cell activation and sensitive organs) or indirect (by calcium homeostasis control) favorable influence on insulin secretion and sensitivity [30]. Osteoporosis is a well-known fact among postmenopausal women, and several risk factors have been linked to this high prevalence, including vitamin, D deficiency [31]. The National, Health and Nutrition, Examination, Survey III (NHANES III) found a link between 25(OH) D and BMD in 13,432 participants, including whites, Hispanics, and blacks [32].…”
Section: Resultsmentioning
confidence: 99%
“…Some research has suggested that vitamin D may have a direct (through its function in pancreatic beta-cell activation and sensitive organs) or indirect (by calcium homeostasis control) favorable influence on insulin secretion and sensitivity [30]. Osteoporosis is a well-known fact among postmenopausal women, and several risk factors have been linked to this high prevalence, including vitamin, D deficiency [31]. The National, Health and Nutrition, Examination, Survey III (NHANES III) found a link between 25(OH) D and BMD in 13,432 participants, including whites, Hispanics, and blacks [32].…”
Section: Resultsmentioning
confidence: 99%
“…13,14 The clinical manifestation of vitamin D deficiency also depends mostly on the degree and duration of the defect, including paresthesia, muscle cramps, bone pain, proximal myopathy, walking difficulty, decreased bone mineral density, and fractures. 15,16 Several studies have shown that vitamin D status is closely linked to the occurrence and development of osteoarthritis and potential adverse effects post-TKA. However, the impact of vitamin D deficiency on early postoperative outcomes in postmenopausal women scheduled for TKA remains unclear.…”
mentioning
confidence: 99%
“…Postmenopausal status and low estrogen levels are associated with joint pain and symptoms, which predominantly occur between the ages of 50 to 59 years 13,14 . The clinical manifestation of vitamin D deficiency also depends mostly on the degree and duration of the defect, including paresthesia, muscle cramps, bone pain, proximal myopathy, walking difficulty, decreased bone mineral density, and fractures 15,16 …”
mentioning
confidence: 99%